1999
DOI: 10.1126/science.283.5409.1897
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Cubic Gadolinium Oxide as a Dielectric for Gallium Arsenide Passivation

Abstract: Epitaxial growth of single-crystal gadolinium oxide dielectric thin films on gallium arsenide is reported. The gadolinium oxide film has a cubic structure isomorphic to manganese oxide and is (110)-oriented in single domain on the (100) gallium arsenide surface. The gadolinium oxide film has a dielectric constant of approximately 10, with low leakage current densities of about 10(-9) to 10(-10) amperes per square centimeter at zero bias. Typical breakdown field is 4 megavolts per centimeter for an oxide film 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
157
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(160 citation statements)
references
References 14 publications
3
157
0
Order By: Relevance
“…At present, it is generally believed that VBO or CBO in ideal MOS device should be greater than 1 eV. 6,[70][71][72][73][74] It is noted that the VBO or CBO calculated by HSE for different MoS 2 thickness is greater than 1 eV. Therefore, we believe that metal/a-Al 2 O 3 /MoS 2 MOS can be an ideal device.…”
Section: Resultsmentioning
confidence: 80%
“…At present, it is generally believed that VBO or CBO in ideal MOS device should be greater than 1 eV. 6,[70][71][72][73][74] It is noted that the VBO or CBO calculated by HSE for different MoS 2 thickness is greater than 1 eV. Therefore, we believe that metal/a-Al 2 O 3 /MoS 2 MOS can be an ideal device.…”
Section: Resultsmentioning
confidence: 80%
“…8 cm -2 eV -1 ). 14 But, still LaLuO 3 has a fairly large lattice mismatch with respect to GaAs (-3.8%), and another concern is that Lu is one of the rarest elements on earth, which would be problematic for large scale fabrication.…”
mentioning
confidence: 96%
“…However, growing epitaxial oxides on GaAs is rather challenging, since GaAs is neither chemically stable nor thermally stable: GaAs can be oxidized easily to form low quality surface oxides that compromise the interface quality; 5 and GaAs starts to lose As over 400 ˚C. 6 Hong et al 7,8 have demonstrated a method of using in-situ electron beam evaporation to grow epitaxial (Ga,Gd) 2 8 which suggests the importance of epitaxy in reducing interfacial defects. 9 However, the frequency dispersion of the capacitance was still fairly large, 8 and the drive current of the inversion-mode MOSFETs made from (Ga,Gd) 2 O 3 /GaAs was less than 1 mA/mm.…”
mentioning
confidence: 99%
“…However starting from the 8th layer and above the stacking order is that of bulk Gd 2 O 3 . The fact that the Gd 2 O 3 film structure is well adapted to the GaAs structure close to the interface suggests that this film will have good passivation properties as confirmed for thinner films [6].…”
Section: Discussionmentioning
confidence: 74%